A qualitative inquiry into the relational process and power on audit committee effectiveness / Naqiah Razak - Naqiah , Razak (2018)
This research transcends Audit Committee (AC) effectiveness studies beyond the traditional agency theory and ‗black box‘ approach. It explores the effect that an AC-Internal Audit Function (IAF) relational process and AC power has on AC effectiveness. The study extends literature on AC processes and provides insight details into AC power and the quality of the relational process between the AC and IAF by incorporating the relational coordination theory and power theory. A qualitative interpretative phenomenology research methodology captured the relational process and power that occurs between the AC and IAF through the process of interviews. The interviews revealed the stories and experiences of ACs and Chief Audit Executives (CAE) of public listed companies (plcs) in Malaysia. This study has positioned the AC-IAF relational process and AC power as a primary construct in understanding how AC can strengthen and monitor the IAF and in turn the IAF can serve as an important resource to the AC. The multivocality of both relational coordination and power theories provide a new framework in understanding the interaction between the AC and IAF and its influence on AC effectiveness. The new framework shows the conceptual links between relationship factors such as shared goals, shared knowledge and mutual respect and its influence on ACs independence and expertise. The framework depicts how a more independent and knowledgeable AC is able to reinforce the support that AC can provide to the IAF subsequently allowing the IAF to generate quality information to the AC. Information generated from the dynamic equation of high-quality communication dimensions and an independent and objective IAF ensures that the AC is better equipped to monitor and make more informed decisions. The exploration of the mutual adjustment of communication and relationship qualities between the two roles facilitates a clearer understanding on how to achieve a quality reciprocal relationship between the two roles and its impact on AC effectiveness. In addition, the framework also depicts how AC power vis-à-vis relational coordination reveals that ACs must understand, develop and exercise their powers in order to develop a positive mutual reinforcement of relational coordination dimensions which subsequently enhances AC effectiveness. By encouraging relationships of shared goals, shared knowledge, mutual respect and high quality communication between the AC and IAF, Malaysian organizations can expect to reduce the cultural norm which emphasizes class distinctions based on the level of authority. This new framework provides organizations the criterion in selecting AC members with the right knowledge, skills and abilities to maintain independence and carry out their power in accordance to their objectives. Regulators and policy makers can make use of the results to enhance or initiate policies that support and reinforce the link between the AC and the IAF. Finally, professional bodies such as the Institute of Internal Audit Malaysia (IIAM) could use the findings in their deliberations of standards and guidance with regards to the AC and IAF as well as the relationship between both parties.